Profiling Public Service Accessibility Based on the Public Transport Infrastructure - Rojas-Bustamante, L.; Alfaro-Aucca, C.; Molero, I.; Aparicio, D.; Nunez-Del-Prado, M. (Springer Science and Business Media Deutschland GmbH, 2023)
Public services are essential to satisfy the needs of healthcare, education, justice, Etc. in citizens’ daily life. Thus, individuals need these services in a certain proximity to their homes. Nonetheless, in big cities, some public services are not close enough. This is especially true for poor individuals who need public transportation to reach such services. To assess the accessibility of individuals to public services using the public transportation system, we propose a methodology to compute profile districts based on the accessibility to different services. We apply our methodology to Lima and Cusco cities in Peru, showing the tool’s utility while being simple to understand. We profile fifty different districts in four groups, allowing policymakers and urban planners to observe the lack of public services to understand the urban dynamics and social exclusion.
Keywords: Public transport; Profiling (computer programming); Business; Public healthcare; Public health; Public service; Service (business); Public relations; Transport engineering; Marketing; Computer science; Political science; Medicine; Engineering; https://purl.org/pe-repo/ocde/ford#5.02.02